Binding in Turkish Nominal Phrases and Phase-Sliding - Murat Özgen (Dilbilim Araştırmaları Dergisi)
There are studies within literature which claim that nominal phrases such as DPs also constitute phases in addition to v*Ps and CPs (Chomsky, 2006; Hiraiwa, 2005; Marantz, 2007; Ott, 2008 and Svenious, 2004 among others). Every phase is subject to a strict locality condition, i.e. Phase Impenetrability Condition (Chomsky, 2001), which forms an opaque domain for external probes. As one of the phenomenon subject to this strict locality, anaphor binding is allowed only within a given phase, since each phase is a local domain for the binding to occur. However, binding in Turkish CPs and DPs behave differently from each other. While the former allows only local reflexive binding, the latter allows distant reflexive binding as well. If DPs are also assumed to be phases, then they must not allow distant reflexive binding. I claim that this problem is an extension of an operation referred to as phase-sliding. It is an operation that extends the phase boundary by pushing up the borders of a spell-out domain (Gallego, 2010). It occurs when a phase head H0 is raised to another head X0 to form a complex [H0+X0]. This study aims to show that this operation accounts for the asymmetry between the binding behaviors of the two phases, i.e. DPs and CPs.